Effect of zinc oxide nanoparticles with matrix metalloproteinase inhibitors on the shear bond strength of a universal dentin bonding agent to caries affected dentin - Divyanshi Agarwal; Srinidhi Surya Raghavendra; Shalini Aggarwal; Neil Lewis; Pushpal Ingle (Journal of Dental Materials and Techniques, 2024)
Objective: This study evaluated the effect of zinc oxide (ZnO) nanoparticles combined with matrix metalloproteinase (MMP) inhibitors on the shear bond strength (SBS) of a universal bonding agent to caries-affected dentin (CAD).Methods: Forty extracted molar teeth were ground to expose dentin. CAD was induced by immersing specimens in 10% citric acid for 4 hours. Samples were divided into five groups (n=8) based on the surface treatment following acid etching: Group 1: CAD treated with hesperidin, Group 2: CAD treated with ZnO nanoparticles and hesperidin, Group 3: CAD treated with grape seed extract, Group 4: CAD treated with ZnO nanoparticles and grape seed extract, and Group V: Control (no surface treatment). G-Premio Bond was applied and then composite resin cylinders were bonded to the dentin surface. After thermocycling, the bond strength of the specimens was measured using a universal testing machine. The data were analyzed by ANOVA and Tukey’s post hoc test, at a significance level of P < 0.05.Results: A significant difference in SBS was observed between the study groups (P < 0.001). Group 2 demonstrated the highest SBS (9.73 ± 0.37 MPa), followed by group 4 (8.76 ± 0.11 MPa), group 1 (7.68 ± 0.27 MPa), and group 3 (6.47 ± 0.34 MPa). The lowest bond strength was observed in the control group (4.32 ± 0.46 MPa).  All pairwise intergroup comparisons were statistically significant (P < 0. 05).Conclusions: Surface treatment with ZnO nanoparticles and MMP inhibitors enhances the bond strength of universal bonding agents to caries-affected dentin.